Ranking of corporate governance dimensions: A Delphi study - Norita Mohd Noor; Amran Rasli; Mas Anom Abdul Rashid; Muhammad Faraz Mubarak; Imelda Hermilinda Abas (Administrative Sciences, 2022)
Most research on Initial Public Offering (IPO) focuses on the financial aspects of a company; previous research on corporate governance tended to focus on factors that influence the company proceeding with IPO. Few researchers studied the aspect of leadership using corporate governance as means to achieve company growth and IPO. This study seeks to identify dimensions deemed as important for corporate governance from the Malaysian perspective by using a two-round Delphi Method. The consistency of the ranking of these dimensions was then determined using Kendall's coefficient of concordance. The order of importance for the nine dimensions uncovered from the Delphi Method are as follows: (1) Leadership; (2) Board Structure; (3) Vision, Mission and Strategies; (4) Policies, Process and Procedures; (5) Transparency; (6) Accountability and Responsibility; (7) Risk management and Internal Control; (8) Culture, and (9) Training and Communication. The interplay of the aforementioned dimensions and corporate governance is presented. Finally, quantitative as well as mixed methods research are recommended for a more in-depth understanding and to reduce bias through triangulation.
Keywords: 350; company growth; corporate governance; Delphi method; Kendal's coefficient of concordance